Thoracic ultrasound for beginners: utility and training issues for clinicians. - Wrightson, J; Maskell, N (2011)
Bedside thoracic ultrasound is gaining popularity among non-radiologists, because of its advantages in the diagnosis and management of pleural disease. However, it has significant potential pitfalls and formal training is essential to avoid harm. This review gives an overview of the utility of ultrasound and discusses training.